Odpowiedzi

2010-01-06T22:00:24+01:00
(-(6 i 7/12-3 i 17/36) × ( -2,7) - 4 i1/3 : 0,65):(-3-(-4))=
(-(237/36-125/36) x (-2,7) - 13/3*10/65):1=
-112/36*(-2,7)-20/3=
42/5-20/3=
126/15-100/15=
26/15
2010-01-06T22:00:58+01:00
W liczniku:
-(6 i 7/12-3 i 17/36) × ( -2,7) - 4 i1/3 : 0,65
w mianowniku
-3-(-4)=

w liczniku
(-79/12 - 125/36) x (27/10) - 13/3: 65/100
w mianowniku
1

-(222)x 27/10 - 13/3 * 100/65=
Najlepsza Odpowiedź!
2010-01-06T22:05:05+01:00
licznik: -(6 i 21/36 - 3 i 17/36)(- 27/10) - 13/3 :13/20= - (237/36- 125/36)(-27/10)- 13/3 * 20/13= -(112/36)(-27/10) -20/3= - (56/12)(-9/5) - 20/3= 504/60 - 20/3= 126/15 -20/3= 126/15 - 100/15= 26/15
mianownik : -3+4=1
wynik: 26/15